1989
DOI: 10.1136/vr.124.10.235
|View full text |Cite
|
Sign up to set email alerts
|

Acute phase response in horses: changes in plasma cation concentrations after localised tissue injury

Abstract: An acute phase reaction was elicited in four horses to which Freund's adjuvant was administered intramuscularly. The localised inflammation was accompanied by changes in the plasma concentrations of copper, iron and zinc. The plasma copper concentration, the plasma ceruloplasmin copper concentration and the ceruloplasmin oxidase activity in the plasma steadily increased to a maximum 24 days after the administration of the adjuvant. At this time, the plasma copper concentration was 2.2 micrograms/ml, a 90 per c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 0 publications
5
34
1
1
Order By: Relevance
“…The edema that persisted at the injection site at the end of the experiment by Mills et al (1998) might have been due to the third injection of FCA on the fifth day of the experiment, despite the lower dosage used by these authors. The rapid increase in local temperature with three statistically significant peaks at 6 h, 30 h, and 60 h PI as well as the observed edema and localized pain not only represent the classical signs of inflammation but are similar to the results obtained using other protocols for intramuscular administration of FCA in horses (Auer et al 1989, Mills et al 1997a, 1997b, Oliveira-Filho et al 2012. Mills et al (1998) observed an elevated temperature in the horses 48 h after the first dose of FCA, which decreased to normal on the fourth day.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The edema that persisted at the injection site at the end of the experiment by Mills et al (1998) might have been due to the third injection of FCA on the fifth day of the experiment, despite the lower dosage used by these authors. The rapid increase in local temperature with three statistically significant peaks at 6 h, 30 h, and 60 h PI as well as the observed edema and localized pain not only represent the classical signs of inflammation but are similar to the results obtained using other protocols for intramuscular administration of FCA in horses (Auer et al 1989, Mills et al 1997a, 1997b, Oliveira-Filho et al 2012. Mills et al (1998) observed an elevated temperature in the horses 48 h after the first dose of FCA, which decreased to normal on the fourth day.…”
Section: Discussionsupporting
confidence: 67%
“…Experimental models using FCA for the induction of inflammatory processes have demonstrated significant decreases in the plasma or serum iron levels in horses (Auer et al 1989, Mills et al 1997a. Recently, we verified that the increase in hepatic hepcidin mRNA expression was likely responsible for the hypoferremia observed in horses after LPS injection (Oliveira-Filho et al 2012).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In contrast, however, systemic copper concentrations are widely reported to increase in response to acute and chronic inflammation (49 -65). Although the secreted copper-containing protein, ceruloplasmin, is partially responsible for this rise in serum copper (66), the non-protein-bound fraction of copper in the serum is also increased during inflammation (49). Moreover, radiotracer studies with 64 Cu have demonstrated that copper accumulates at sites of inflammation (67) and within the exudates of wounds and burns where there exists an abundance of macrophages (68,69).…”
Section: Discussionmentioning
confidence: 99%
“…Die systemische APR besteht unter anderem aus Fieber, Leukozytose, gesteigerter Glukokortikoidsekretion, Konzentrationsänderungen von Eisen, Zink und Kupfer im Blut und in der Leber, Aktivierung der Gerinnung, des Komplementsystems, des Kininsystems und der Fibrinolyse, einer negativen Stikkstoffbilanz, Veränderungen des Aminosäurestoffwechsels und insbesondere aus drastischen Veränderungen der Plasmaproteinzusammensetzung (Koj et al 1988, Kushner et al 1989, Auer et al 1989. Auch das Endokrinium ist von den Verän-derungen während der APR betroffen.…”
unclassified